Carbazole‐based conjugated polymer covalently coated Fe3O4 nanoparticle as efficient and reversible Hg2+ optical probe. Issue 17 (3rd June 2013) - Tian, Yong; Shi, Wei; Luo, Jianmin; Ma, Fudong; Mi, Hongyu; Lei, Yanli
ABSTRACT A type of fluorescent–magnetic dual‐function nanocomposite, Fe3O4@SiO2@P‐2, was successfully obtained by Cu+‐catalyzed click reaction between acetylene (CCH)‐substituted carbazole‐based conjugated polymer (P‐2) and azide‐terminated silica‐coated magnetic iron oxide nanoparticles (Fe3O4@SiO2–N3). Optical and magnetization analyses indicate that Fe3O4@SiO2@P‐2 exhibits stable fluorescence and rapid magnetic response. The fluorescence of Fe3O4@SiO2@P‐2 was quenched significantly in the presence of I− and gave a detection limit (DL) of ∼8.85 × 10−7 M. Given the high binding constant and matching ratio between Hg2+ and I−, the fluorescence of Fe3O4@SiO2@P‐2/I− complex recovered efficiently with the addition of Hg2+. A DL of ∼4.17 × 10−7 M was obtained by this probing system. Recycling of Fe3O4@SiO2@P‐2 probe was readily achieved by simple magnetic separation. Results indicate that Fe3O4@SiO2@P‐2 can be used as an "on–off–on" fluorescent switchable and recyclable Hg2+ probe. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3636–3645